(untitled) (Eurasian Research Bulletin, 2024)
This article describes the operations of addition, subtraction, multiplication and division on number systems. Also, the representation of the numbers in the decimal number system in the binary number system and the ways to transfer the numbers from the binary number system to the decimal number system are presented